2018
DOI: 10.1108/wjemsd-03-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting talent management for sustainable development in Africa

Abstract: Purpose-With the steady overall development of the continent, the African business landscape over the last decade has witnessed increased growth through numerous avenues. Growth has been through the emergence of formalised small and medium enterprises, the growth of business and transition from one scale to another as well as inward foreign direct investment. The purpose of this paper is to investigate how this business growth can be sustained, particularly in the area of talent management, within the framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…TM promotes organizational performance (Kehinde, 2012) and workforce productivity (Zadeh & Ahmadi, 2017), and helps the organization to solve problems more effectively (Poorhosseinzadeh & Subramaniam, 2012). TM helps fims to be more adaptable and proactive within the fast changing environment (Sareen & Mishra, 2016), and assists in sustaining business growth (Mwila & Turay, 2018). TM relates to leadership programs in that a talent can be merged with leadership roles, hence guides an organization to better production and business levels in terms of employee relations (Unseem, 2011).…”
Section: Talent Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…TM promotes organizational performance (Kehinde, 2012) and workforce productivity (Zadeh & Ahmadi, 2017), and helps the organization to solve problems more effectively (Poorhosseinzadeh & Subramaniam, 2012). TM helps fims to be more adaptable and proactive within the fast changing environment (Sareen & Mishra, 2016), and assists in sustaining business growth (Mwila & Turay, 2018). TM relates to leadership programs in that a talent can be merged with leadership roles, hence guides an organization to better production and business levels in terms of employee relations (Unseem, 2011).…”
Section: Talent Managementmentioning
confidence: 99%
“…OI which means the capability to create and utilize brain power in achieving organizational goals and missions represents the organization's talent (Nasiri et al, 2013). Therefore, TM potential is best revealed through measures of intelligence (Mwila & Turay, 2018).…”
Section: Relation Between Talent Management and Organizational Intellmentioning
confidence: 99%
“…Although there are examples of success, challenges with identifying and hiring the right talent continues to be difficult. Mwila and Turay () found that the talent needs of the continent have evolved, resulting in noticeable voids with businesses being unable to fill their employment vacancies with appropriate talent. According to a PwC survey, around 80% of African CEOs see lack of talent as a threat to growth (Mugan, ).…”
Section: Silicon Valley Versus Africamentioning
confidence: 99%
“…The African business landscape over the last decade has witnessed increase through the emergence of formalized small and medium enterprises, the growth of business and transition from one scale to another as well as inward FDI (Mwila and Turay, 2018). However, the challenge is how this business growth can be sustained, particularly by TM in Africa.…”
Section: Tm For Sies and Global Migrationmentioning
confidence: 99%
“…TM is among the competencies that have the poorest application in African workplaces (Schutte et al , 2015) – in particular hiring practices are criticized for being too rigid (World Economic Forum, 2011). This rigidity is manifested in leaving talent behind, perpetuating the cycle of poverty, stunting economic growth and minimal business’ contribution for attaining the sustainable United Nations’ development goals drawn for most African countries (Mwila and Turay, 2018).…”
Section: Tm For Sies and Global Migrationmentioning
confidence: 99%